Content of phenolic compounds and antioxidant in different parts of Misai Kucing (Orthosiphon Stamineus) grown under different light intensity - Mohd Farhan Abdul Razak (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Content of phenolic compounds and antioxidant activity in different parts of misai kucing such as leaves, roots and stem has been observed when the misai kucing is treated in different light intensity. Total phenolic content and antioxidant activity has been determined using Folin- Ciocalteu method and DPPH method respectively. The results show that for total phenolic content analysis, the phenolic compound has been detected to be mostly in leaves compared to stem and roots. For antioxidant activity test, high antioxidant activity had been observed in roots compare to leaves and stem. Besides, light intensity has been observed to affect the total phenolic content and antioxidant activity in misai kucing. The results show that phenolic compounds and antioxidant activity become higher for misai kucing planted in open environment compared to misai kucing planted in shade. As a conclusion, leaves contain high phenolic compounds while roots gain highest antioxidant activity. Besides, light intensity factor have affected the content of total phenolic and antioxidant activity of misai kucing.